Structural Characterization of a Low Molecular Weight HG-Type Pectin From Gougunao Green Tea - Hong, Tao; Zhao, Jiaying; Yin, Junyi; Nie, Shaoping; Xie, Mingyong (Frontiers in Nutrition, 2022)
Tea is a popular beverage with a long history of safe and healthy use. Tea polysaccharide is a bioactive component extracted from tea, which has attracted more and more attention in recent decades. In this paper, an acidic polysaccharide GPS was isolated from green tea leaves. After purification, several homogalacturonan (HG) and rhamnogalacturonan-I (RG-I) fractions were obtained. Fraction GPS2b with the highest yield was selected for structural characterization by methylation and NMR analysis. GPS2b was found to be a HG type pectic polysaccharide with low molecular weight. It was mainly composed of →4)-α-GalpA- (1→ and →4)-α-GalpA-6-OMe-(1→ in a molar ratio of 1:1. In addition, minor highly branched RG I domain was identified in this fraction. The investigation of structure features of tea polysaccharide can provide insights to understand its structure-bioactivity relationship.